Pemanfaatan IPTEK Melalui Website sebagai Upaya Scale Up pada Kelompok UMKM Semabu Desa Pasir Jambu - Sekarini, Ratih Ayu; Mintarsih , Mimin; Farhana, Farhana; Trisista, Ratna Galuh Manika; Wiwin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: MSMEs play an important role in the village economy, but fierce competition demands more effective marketing strategies. This research aims to improve the competitiveness of MSMEs through the utilisation of science and technology as a scale-up effort, with a case study on Semabu MSMEs in Pasir Jambu Village, Bandung. Methods: Research methods 1) identifying needs analysis 2) website creation and management 3) training and digital literacy and website-based marketing 4) mentoring and periodic evaluation and 5) implementation models that can be developed Results: After the implementation of the website-based marketing strategy, there was a significant increase in the number of new customers as well as sales growth. The success of the Semabu MSME group in competing in the Pasir Jambu Village environment can be attributed to the utilisation of the https://www.sihalal-semabu.com/ platform, effective use of social media, attractive product displays, and direct interaction with customers through online platforms. Conclusion: Understanding and skills in implementing online marketing strategies among business owners, especially the Semabu MSME group in Pasir Jambu Village, are crucial factors in the success of their businesses, especially in facing competition in the digital era